Efficiency‐based approach to quantifying 'tuneability' performance in frequency‐agile narrowband antennas. Issue 1 (18th October 2019) - James, Oliver; Hilton, Geoff; Beach, Mark
Abstract : Many communications systems require reconfigurable band access in compact form factors. Contemporary literature routinely reports 'tuneability' (or frequency agility) in input response terms ( S 11 ), yet repeatable efficiency data were reported in <40% of cases surveyed. Despite the low efficiencies associated with many tuneable narrowband antennas, e.g. electrically small antennas (ESAs), reference methods to quantify tuneability in terms of a tuned range of realised antenna efficiency, average efficiency in the band and integrated efficiency–bandwidth product do not exist and thus have not been widely adopted. Here, these metrics have been formulated for general application to efficiency‐based tuneability assessment of narrowband antennas. Application to a set of fixed‐frequency/varactor‐tuned ESAs ( ka = 0.19–0.31) in the ultra‐high frequency band is demonstrated. Tuning range of 10% or 25% realised efficiency was found to be several times narrower than S 11 < −6 dB tuning range for antennas in this study and in the literature, highlighting the need for a shift to efficiency‐based tuneability reporting in support of RF system design analysis. The integrated efficiency–bandwidth product has been demonstrated for combined efficiency and reconfigurability comparison of tuneable antennas, providing a platform for future performance grading of a diverse range of antenna tuning technologies.